The prevalence of childhood victimization experienced outside of the family: findings from an English prevalence study - Jackson, Vicki; Browne, Kevin; Joseph, Stephen (Elsevier, 2016)
There has been little research carried out in the United Kingdom (UK) aimed at providing a holistic exploration of the victim experiences of young people within the school and community environments (extrafamilial victimization). This study therefore examined the prevalence of 24 different types of extrafamilial victimization experienced by a sample of 730 young people, aged 13–16 years (mean 13.8 years), from one county in the UK. The findings show that the vast majority of young people experienced some form of extrafamilial victimization over their lifetime (84.1%) and past year (67.2%). Looking at individual categories of victimization experienced over the lifetime, 7 out of 10 young people witnessed or experienced indirect victimization, 1 in 3 experienced property victimization, more than 1 in 4 physical victimization, almost 1 in 2 experienced bullying, 1 in 28 dating violence and 1 in 7 experienced sexual victimization. The findings also suggest that victimization is not an isolated event; participants experienced an average 2.8 different types of victimization across their lifetime. These research findings are compared to those from national victimization surveys in the USA and UK to compile a picture of the victimization prevalence rates across studies. The findings highlight the importance of adopting a holistic approach to the exploration of extrafamilial victimization in future research, assessment of victim experiences, and prevention of extrafamilial victimization.